Air-Masses and fronts in the Monsoon Depression in India - Desai, B.N.; Koteswaram, P. (MAUSAM, 1951)
From a synoptic and aerological studt of the data of radiosonde acents at Vizagapatam, Cuttack, Culcutta and Akyab during a depression in the Bay of Bengal in the beginning of July 1945, it is observed that different airmasses took part in both in the formation stage of the depression and during its subsequent intensification into a storm and movement westnorth westwards. The study supports the mechanism of the formation of depression in the north bay of Bengal during the monsoon season suggested by Desai in an earlier paper.